Using the indigenous technology of making oshikundu to mediate learning of the topic diffusion in Namibia - Endjala, Alma Panduleni (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
The Namibian Science curriculum acknowledges that indigenous knowledge (IK) is an important basis for learning science. Among the shared reasons is that it provides learners with access to abstract scientific concepts. As a result, teachers are encouraged to integrate IK into the teaching and learning of science. However, it seems that there are no explicit guidelines on how IK should be integrated into science classrooms. It is against this backdrop that this study sought to explore how the indigenous technology of making oshikundu (a non-alcoholic beverage) can be mobilised by Grade 8 Life Science teachers to mediate learning of diffusion in their classrooms. The study was underpinned by interpretive and indigenous research paradigms. Within these paradigms, a qualitative case study approach was employed. Four Grade 8 Life Science teachers from four different schools in Okahandja town, Otjozondjupa Region, Namibia, participated in this study. Additionally, an expert community member who was knowledgeable about the indigenous technology of making oshikundu was requested to demonstrate how to make it. In this event, the Life Science teachers had to identify the science concepts embedded in the practice. To gather data, this study made use of semi-structured interviews, workshop discussions, observations and journal reflections. Vygotsky's sociocultural theory was used as a theoretical framework and Mavhunga and Rollnick's topic-specific pedagogical content knowledge (TSPCK) was used as an analytical framework. The findings of this study revealed that the teachers' understanding was positively influenced by the integration of IK which certainly assisted them to relate better to the concept of diffusion. This was validated when teachers extracted emerging science concepts from the indigenous technology of making oshikundu. The implication of this study is that expert community member presentations can greatly enhance sense making of science concepts. The study thus recommends that school-based teachers' continuing professional development in collaboration with expert community members should be carried out to enhance both the teachers' subject content knowledge and pedagogical content knowledge on IK integration.
Keywords: Culturally relevant pedagogy-- Namibia; Diffusion-- Study and teaching (Secondary) Activity programs-- Namibia; Ethnoscience-- Namibia; Pedagogical content knowledge; Social learning; Science teachers Education (Continuing education); Oshikundu